Sleep and neuropsychological performance in HIV+ subjects on efavirenz-based therapy and response to switch in therapy. Issue 4 (4th July 2018) - Shikuma, Cecilia M.; Kohorn, Lindsay; Paul, Robert; Chow, Dominic C.; Kallianpur, Kalpana J.; Walker, Maegen; Souza, Scott; Gangcuangco, Louie Mar A.; Nakamoto, Beau K.; Pien, Francis D.; Duerler, Timothy; Castro, Linda; et al.
Abstract : The antiretroviral drug efavirenz (EFV) has been linked to disordered sleep and cognitive abnormalities. We examined sleep and cognitive function and subsequent changes following switch to an alternative integrase inhibitor-based regimen. Thirty-two HIV-infected individuals on EFV, emtricitabine, and tenofovir (EFV/FTC/TDF) without traditional risk factors for obstructive sleep apnea (OSA) were randomized 2:1 to switch to elvitegravir/cobicistat/emtricitabine/tenofovir (EVG/COBI/FTC/TDF) or to continue EFV/FTC/TDF therapy for 12 weeks. Overnight polysomnography and standardized sleep and neuropsychological assessments were performed at baseline and at 12 weeks. No significant differences in change over 12 weeks were noted between the two arms in any sleep or neuropsychological test parameter. At entry, however, the rate of sleep disordered breathing (SDB) was substantially higher in study subjects compared to published age-matched norms and resulted in a high assessed OSA rate of 59.4%. Respiratory Disturbance Index (RDI), a measure of SDB, correlated with age- and education-adjusted global neuropsychological Z -score (NPZ) ( r  = −0.35, p  = 0.05). Sleep Maintenance Efficiency, Wake after Sleep Onset, REM Sleep and RDI correlated with domain-specific NPZ for learning and memory (all p -values ≤ 0.05). Among HIV-infected individuals on EFV-based therapy and without traditional risk factors for OSA, sleep and neuropsychological abnormalities do not readily reverse after discontinuation of EFV. High baseline rates of SDB and abnormalities in sleep architecture exist in this population correlating with neuropsychological impairment. The role of HIV immuno-virologic or lifestyle factors as contributing etiologies should be explored. OSA may be an under-recognized etiology for cognitive dysfunction during chronic HIV.